Actitudes de padres mexicanos acerca de la igualdad de género en los roles y liderazgos familiares - Ojeda, Norma; González Ramírez, Raúl (El Colegio de México A.C., 2018)
We analyze the parents’ attitudes on gender equality regarding family roles and leaderships in the urban-popular sectors of Tijuana, Mexico. We use the Survey of Parents with Children in Junior High-schools in Tijuana, B.C., 2015, that includes information for 2 560 parents with children attending public junior high schools. Four indexes are designed that intend to measure gender equality regarding the maternity role, domestic roles and family leaderships. Logistic regression models are also estimated. The findings indicate coexistence of a great value assigned to the maternity role in women’s life, plus moderately enthusiastic attitudes in favor of gender equality in the domestic roles, but less enthusiastic about sharing and switching family leaderships. The level of education showed to be the only variable statistically significant across the four indexes.